Chapter Eighteen: Sharing Power: Māori and Protect Areas - Mead, Aroha Te Pareake (Future challenges for Māori: he kōrero anamata, 2013)
"This collection of essays by 22 contributors, experts in their fields, represents the accumulated knowledge of a group of Māori scholars on a variety of contemporary issues, including Māori identity and self-determination, the environment, te reo Māori, education, social and economic issues, and governance and leadership. The collection is a result of a series of seminars organised by the MANU AO Academy, which is a national inter-university Māori Academy for academic and professional advancement"--Publisher information.
Keywords: government; mana motuhake; rangatiratanga; social conditions; sovereignty

Chapter 7: Papaki Rua Ngā Tai: Tides of Confluence: Māori and the State - Durie, Mason (Ngā tai matatū: tides of Māori endurance, 2005)
"Nga Tai Matatu: Tides of Maori Endurance describes and analyses the position of the Maori people and Maori interests at the start of the third millennium. It also recognises the journeys from the past and makes projections into the future. The book builds on the highly successful Te Mana, Te Kawanatanga: The Politics of Maori Self-Determination but also introduces new issues and canvasses recent developments that have influenced Maori lives and Maori resources. Development is an ongoing process that has distant beginnings and no real ending. That sense of eternity is reflected in the Maori title; like the changing nature of the tide, Maori fortunes also change."--Book jacket.
Keywords: UNDRIP; crown policy; government relations; land tenure; law; mana motuhake; sovereignty; tino rangatiratanga; welfare policies

Chapter 8: Te Ngau o te Tai: The Sting of the Tide: Māori and the Law - Durie, Mason (Ngā tai matatū: tides of Māori endurance, 2005)
"Nga Tai Matatu: Tides of Maori Endurance describes and analyses the position of the Maori people and Maori interests at the start of the third millennium. It also recognises the journeys from the past and makes projections into the future. The book builds on the highly successful Te Mana, Te Kawanatanga: The Politics of Maori Self-Determination but also introduces new issues and canvasses recent developments that have influenced Maori lives and Maori resources. Development is an ongoing process that has distant beginnings and no real ending. That sense of eternity is reflected in the Maori title; like the changing nature of the tide, Maori fortunes also change."--Book jacket.
Keywords: government relations; law; mana motuhake; sovereignty; tino rangatiratanga; tiriti o waitangi/treaty of waitangi

Chapter 9: Rongotai: the Roar of the Ride: Māori in Parliament - Durie, Mason (Ngā tai matatū: tides of Māori endurance, 2005)
"Nga Tai Matatu: Tides of Maori Endurance describes and analyses the position of the Maori people and Maori interests at the start of the third millennium. It also recognises the journeys from the past and makes projections into the future. The book builds on the highly successful Te Mana, Te Kawanatanga: The Politics of Maori Self-Determination but also introduces new issues and canvasses recent developments that have influenced Maori lives and Maori resources. Development is an ongoing process that has distant beginnings and no real ending. That sense of eternity is reflected in the Maori title; like the changing nature of the tide, Maori fortunes also change."--Book jacket.
Keywords: government relations; kāwanatanga; law; mana motuhake; māori electorates; māori seats; parliament; self-determination; sovereignty; tino rangatiratanga

The history of Kotahitanga - Walker, Ranginui (Waitangi 1984: a turning point? : a report to the New Zealand churches concerning the Treaty of Waitangi, its observance, and its ceremonial commemoration., 1984)
Keywords: kotahitanga; mana motuhake; religion; tiriti o waitangi/treaty of waitangi

Māori Political Representation: A Case for Change - Mahuta, Robert (Maori Representation in Parliament, 1982)
Keywords: mana motuhake; māori electorates; māori seats; population; voting

Mana Maori motuhake Maori concepts and practices of sovereignty - Mutu, Margaret (Routledge handbook of critical indigenous studies, 2021)
Keywords: colonisation; ethnicity; he whakaputanga; mana motuhake; rangatiratanga

Chapter Six: Māori and Freshwater Law - Ruru, Jacinta (Future challenges for Māori: he kōrero anamata, 2013)
"This collection of essays by 22 contributors, experts in their fields, represents the accumulated knowledge of a group of Māori scholars on a variety of contemporary issues, including Māori identity and self-determination, the environment, te reo Māori, education, social and economic issues, and governance and leadership. The collection is a result of a series of seminars organised by the MANU AO Academy, which is a national inter-university Māori Academy for academic and professional advancement"--Publisher information.
Keywords: government; mana motuhake; rangatiratanga; social conditions; sovereignty

Chapter 5: He Pōkeke Uenuku i Tu Ai: The Evolution of Contemporary Māori Protest - Poata-Smith, Evan (Nga Patai : Racism and Ethnic Relations in Aotearoa New Zealand, 1996)
The evolution of contemporary indigenous protest in Aotearoa/New Zealand.
Keywords: activism; mana motuhake; protest; rangatiratanga

Indigenous Rights, Poetry and Decarceration - McIntosh, Tracey (Human Rights and Incarceration, 2018)
Keywords: incarceration; indigenous soveriegnty; mana motuhake; māori rights; rangatiratanga